A Taste for Brown Bodies : Gay Modernity and Cosmopolitan Desire - Perez, Hiram (Book collections on Project MUSE., 2015)
Neither queer theory nor queer activism has fully reckoned with the role of race in the emergence of the modern gay subject. In 'A Taste for Brown Bodies', Hiram Perez traces the development of gay modernity and its continued romanticization of the brown body. Focusing in particular on three figures with elusive queer histories - the sailor, the soldier, and the cowboy - Perez unpacks how each has been memorialized and desired for their heroic masculinity while at the same time functioning as agents for the expansion of the US borders and neocolonial zones of influence.